Legal Politics For The Establishment Of Yogyakarta Regional Regulation Number 2 Year 2017 Regarding No-Smoking Area Siyasah Dusturiyyah Perspective - Aris Darmawan Al Habib (International Journal of Transdisciplinary Knowledge, 2021)
This research is normative legal research with a statutory approach which aims to analyze and describe the legal politics of the formation of the Yogyakarta City Regional Regulation Number 2 of 2017 concerning the Siyāsah dusturiyyah perspective on smoke-free areas. The type of data used in this study is material law consisting of primary, secondary, and tertiary legal materials. The data analysis method used is descriptive-analytic, and data collection uses library research. This study shows that first, the establishment of the Yogyakarta City Regional Regulation Number 2 of 2017 concerning Non-Smoking Areas is coloured by the democratic political configuration by the pros and cons of the Yogyakarta City government. Second, the Yogyakarta City Regional Regulation Number 2 of 2017 concerning Non-Smoking Areas substantially follows the principle of siyāsah dusturiyyah, reflecting the value of justice and legal certainty.